2010
DOI: 10.3802/jgo.2010.21.2.112
|View full text |Cite
|
Sign up to set email alerts
|

Wine drinking and epithelial ovarian cancer risk: a meta-analysis

Abstract: Objective: Wine has been the focus in the prevention of epithelial ovarian cancer (EOC) development because resveratrol abundant in wine has anti-carcinogenic properties. However, epidemiologic results have been heterogenous in the chemopreventive effect of wine on the development of EOC. Thus, we performed a meta-analysis for comparing EOC risk between wine and never drinkers using previous related studies. Methods: After extensive search of the literature between January 1986 and December 2008, we analyzed 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…A pooled analysis of 10 cohort studies that included over 500,000 women and 2,001 incident OC cases also observed no risk association with total alcohol intake (pooled multivariate RR=1.12, 95% CI: 0.86–1.44 comparing > 30 to 0 g of alcohol per day) or alcohol intake from wine, beer, or spirits 322 . There was no association (OR=1.13, 95% CI: 0.92–1.38) between wine consumption and OC risk in a recent meta-analysis of 10 studies (3 cohort and 7 case-control studies) with 135,871 women, including 65,578 wine drinkers 323 . Based on these data, it seems reasonable to conclude that if alcohol intake does influence risk of OC, the magnitude is small and possibly limited to particular histologic subtypes.…”
Section: Risk Factors and Preventive Factorsmentioning
confidence: 99%
“…A pooled analysis of 10 cohort studies that included over 500,000 women and 2,001 incident OC cases also observed no risk association with total alcohol intake (pooled multivariate RR=1.12, 95% CI: 0.86–1.44 comparing > 30 to 0 g of alcohol per day) or alcohol intake from wine, beer, or spirits 322 . There was no association (OR=1.13, 95% CI: 0.92–1.38) between wine consumption and OC risk in a recent meta-analysis of 10 studies (3 cohort and 7 case-control studies) with 135,871 women, including 65,578 wine drinkers 323 . Based on these data, it seems reasonable to conclude that if alcohol intake does influence risk of OC, the magnitude is small and possibly limited to particular histologic subtypes.…”
Section: Risk Factors and Preventive Factorsmentioning
confidence: 99%
“…We identified 72 eligible publications that included 212 meta-analyses of 1853 individual study estimates exploring associations between non-genetic risk factors and the risk of developing or dying from ovarian cancer ( Figure 1 ) [ 8 , 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 …”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis by Kim et al assessed the relationship between wine consumption and ovarian cancer risk. An analysis of 10 studies (three cohort studies and seven clinical control studies) did not show the association between wine consumption and a reduction in the risk of ovarian cancer (OR = 1.13, 95% CI = 0.92–1.38) [ 177 ]. However, the insufficient number of epidemiological studies assessing the effect of resveratrol on the risk of ovarian cancer does not allow to draw clear conclusions.…”
Section: Phytochemicals In Ovarian Cancer Preventionmentioning
confidence: 99%